Governance Structures and Mechanisms in Public Service Organizations Theories, Evidence and Future Directions - Calabrò, Andrea (Contributions to Management Science, 2011)
This book addresses the nexus of issues exploring governance structures and mechanisms in public service organizations, thus contributing to the development of disciplines that focus on public management. It goes beyond the state of the art by addressing a number of specific issues in a more systematic fashion. The book's interdisciplinary focus is a particularly valuable asset, as its topic is situated at the crossroads of a number of fields, including public management, business administration, corporate governance, policy studies, political science, sociology, and third sector studies, all of which offer important perspectives and are important for the development of public management and public services. The book covers more than Italy and Norway and focuses specifically on public service organizations, addressing more aspects of their governance structures and mechanisms than any other book available today. The unique presentation of features related to the governance and management of different actors (state-owned enterprises, local public utilities, ministries, municipalities, citizens, etc.), involved at different levels in the production and provision of public services, makes it possible to compare and contrast these different perspectives and opens new avenues of theoretical collaboration and developmen